Mapping Leachate Contamination Using 2D Electrical Resistivity Tomography and Self-Potential Methods at Kebon Kongok Landfill, Lombok, Indonesia - Agustina Maryofa Hernanu; Suhayat Minardi; Syamsuddin Syamsuddin (Journal Electrical and Computer Experiences, 2026)
Leachate migration from municipal solid waste landfills poses a persistent threat to soil and groundwater because leachate commonly contains dissolved organic matter, inorganic ions, ammonia, and trace metals. This study maps leachate contamination beneath and around Kebon Kongok Landfill, West Lombok, Indonesia, using two complementary geoelectrical techniques: two-dimensional electrical resistivity tomography (ERT) with the Wenner configuration and self-potential (SP) mapping with a fixed-base technique. ERT measurements were acquired along seven survey lines around the landfill and the adjacent settlement boundary, while SP observations were used to infer the preferential direction of subsurface flow. The inverted ERT sections show widespread low-resistivity anomalies interpreted as leachate-contaminated zones, with characteristic resistivity values of 0.43-10.70 Ω m. Contamination was detected from near-surface layers to a maximum interpreted depth of 19.8 m. The SP contour map indicates low-potential anomalies of approximately -30 to -20 mV in the eastern sector, suggesting that the leachate plume migrates predominantly from the landfill area in the west toward residential areas in the east. These findings demonstrate that the integration of ERT and SP methods provides an effective non-invasive approach for delineating leachate distribution and supporting groundwater-risk management around active landfills.